In-situ electrostatic field regulating the recrystallization behavior of P(VDF-TrFE) films with high β-phase content and enhanced piezoelectric properties towards flexible wireless biosensing device applications. (September 2022) - Lv, Fu; Lin, Jiamin; Zhou, Zheng; Hong, Zijian; Wu, Yongjun; Ren, Zhaohui; Zhang, Qilong; Dong, Shurong; Luo, Jikui; Shi, Junhui; Chen, Ruimin; Liu, Bing; et al.
Abstract: Fabrication of flexible piezoelectric polymers is essential for the development of wearable biosensors. Nevertheless, the piezoelectric coefficient of polymers is usually an order of magnitude lower than the inorganic piezoelectric materials, which limits the miniature of the devices. Herein, a simple and cost-effective technique is proposed by applying an electrostatic field to in-situ regulate the recrystallization behavior of the poly(vinylidene fluoride-trifluorethylene) (P(VDF-TrFE)) film during the thermal annealing and recrystallization stage. Significantly enhanced properties are obtained, including a large piezoelectric coefficient (d33 30.7 pC/N) and a high voltage sensitivity of 167.12 mV/kPa. The outstanding performance is mainly attributed to the applied electrostatic field maintained during the film growth stage, which promotes the generation of nucleation sites for the polar β lamellae crystals. A wireless sensor system is further established with the obtained P(VDF-TrFE) film, demonstrating great potential applications in movement monitoring. The proposed facile approach could potentially be applied to the large-scale production of polymer films with excellent piezoelectric properties for flexible wireless biosensing device applications. Graphical Abstract: This work shows that the electrostatic field can effectively in-situ regulate the recrystallization behaviors of PVTF piezo-films, forming more polar β lamellae crystals with smaller size. The increased crystallinity enables the PVTF films to possess better piezoelectric and ferroelectric properties. The PVTF films also show excellent pressure sensitivity, exhibiting great potential applications in movement and safety real-time monitoring. ga1 Highlights: Regulate the recrystallization behavior of P(VDF-TrFE) films by electrostatic field. Enhanced piezoelectric properties were realized with high β -phase content. The facile approach is highly desirable for large-scale production of piezo-films.